Housing, refreshing challenges. Update: modernization to current time. Refresh: make it work again. - Chumpitaz Mellarez, Felipe (2023)
The demand for a domestic space according to the social and urban dynamics requires the updating of housing. Faced with this panorama, proposals have emerged that demonstrate that variability and mutability provide housing with forceful improvements; for this reason, concepts such as flexibility, industrialization and the theory of supports are alluded to. This article collects examples, national and international, in which these concepts have sought their physical materialization to demonstrate the relevance of unique, participatory, and variable housing. In this sense, this work is constituted as a reflection on housing and what it could become, from a broad perspective that considers current circumstances and explores its ideation and future construction.